Feasibility studies of solar energy as an alternative energy resource for Muscat international airport - Sreejaya, K.V.; Khalid Mubarak, Abdullah Al-Haddabi (INTI International University, 2020)
Airports have gained an important position in the modern world and is integral to connecting near and far corners of the world. The airports are also energy intensive and consume large quantities of electricity. This can place a great burden on the limited oil and gas reserves across the world. Converting fuel sources in the aviation sector can eliminate a large proportion of conventional energy usage. In this study, a grid-connected solar PV power plant is proposed for the new Muscat International Airport terminal. The electricity consumption of the airport is estimated using available equations. The software SISIFO is used to develop and simulate a PV power plant for the airport against live values of solar irradiation and temperature data. It was found that the monthly and annual values of power yield is sufficient to fulfill the energy needs of the airport and can be used to feed to the main electricity grid for local power supply and supply of power to the airport during winter months. Overall, the results established the general feasibility of a grid-connected PV system for the Muscat International airport. The PV system does not require a lot of maintenance. It also has a lengthy life of 25 years and can reduce the energy burdens in oil and gas reserves. The solar irradiance values, temperature and electricity yield of a solar power plant, as was seen from the results, is heavily dependent on the seasonal and daily variations in solar energy.